Evaluation of efficacy of Arrowroot (Marantaarundinacea) extract incorporated synbiotic ice-cream - Jayatilake, S. (International Journal of Psychosocial Rehabilitation, 2020)
Arrowroot (Marantaarundinacea) is astarchy root which stated to comprisesignificantquantity of Fructooligosaccahrides in their extract. Due to the high production costs of commercial prebiotics, arrowroot extract has a potential to develop as a low cost, reliable, sustainable prebiotic source for the functional food industry. Therefore, this study was done to assesstheprebiotic activity of arrowroot extract and to assesstheLactobacillus cell viability in arrowroot extract incorporated synbiotic ice-cream during frozen storage. Based on the results, the highest prebiotic activity was given by the arrowroot extract compared to inulin and glucose. The prebiotic activity of arrowroot extract and inulin were significantly higher than the prebiotic activity of glucose (p0.05). The probiotic cell viability is more or less same in sample (arrowroot) and reference (inulin) ice-creams, the lowest probiotic cell viability was recorded in the control ice-cream, but there is no any significant difference in the probiotic cell viabilities in all three ice-cream types during frozen storage (p>0.05). According to the physiochemical results, there is a significant difference in total soluble solids (TSS) and titratable acidity (TA) between control and reference ice creams (p0.05). Therefore, the prebiotic activity results concluded that there is no significant difference in prebiotic activities of arrowroot extract and inulin. It shows that arrowroot extract has a potential to replace commercial prebiotics like inulin. Probiotic viability results concluded that the prebiotics incorporated ice-creams are having higher cell viabilities than control ice-cream. It indicates that the prebiotic substances had helped probiotics to survive during harsh frozen storage conditions.